2015
DOI: 10.1017/s0950268815002721
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution characteristics of high-risk human papillomaviruses in women from Shanghai, China

Abstract: High-risk human papillomaviruses (HPVs) are highly prevalent worldwide, and HPV genotype distribution varies regionally. Molecular surveys of HPVs are important for effective HPV control and prevention. Fifteen high-risk HPV strains (16, 18, 31, 33, 35, 39, 45, 51, 52, 53, 56, 58, 59, 66, 68) and six low-risk HPV strains (HPV6, 11, 42, 43, 44, CP8304) were detected by cervical cytology from 10 501 subjects. High-risk HPVs, low-risk HPVs, and both high- and low-risk HPVs were detected in 14·5%, 2·8%, and 2·4% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
(71 reference statements)
4
20
1
1
Order By: Relevance
“…HPV 52 is the most common HR‐HPV genotype, followed by HPVs 16, 58, 39, and 51. These findings are partly consistent with the data on HPV prevalence in Asian regions such as Japan, Taiwan and Shanghai, where the most common HPVs are ranked HPVs 52, 16, 51, 35, and 18 and HPVs 52, 16, 58, 53, and 33 . Given that China covers a vast territory, the prevalence patterns differ regionally, even among different regions of mainland China.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…HPV 52 is the most common HR‐HPV genotype, followed by HPVs 16, 58, 39, and 51. These findings are partly consistent with the data on HPV prevalence in Asian regions such as Japan, Taiwan and Shanghai, where the most common HPVs are ranked HPVs 52, 16, 51, 35, and 18 and HPVs 52, 16, 58, 53, and 33 . Given that China covers a vast territory, the prevalence patterns differ regionally, even among different regions of mainland China.…”
Section: Discussionsupporting
confidence: 88%
“…5 HPVs preferentially infect the mucosa of the genitals, upper-respiratory tract, and the skin, 6 and they are recognized as important pathogenic factors of cervical cancer and precancerous lesions. 6,7 Based on the association of HPV with cervical cancer or the risk of carcinogenesis, all HPV genotypes can be divided into different subgroups of mucosal HPVs: high-risk types of HPVs (HR-HPV), such as HPVs 16,18,31,33,35,39,45,51,52,56,58,59,68,73,and 82, which are classified as carcinogenic to humans 5,8 ; low-risk types of HPVs (LR-HPV), such as HPVs 6,11,28,32,40,42,43,44,54,55,57,61,62,71,72,74,81,83,84,86,87, and 89; probable/possible HR-HPVs (pHR-HPV), such as HPVs 68, 26, 53, 66, 82, 70, 67, and 73. 5 The HR-HPVs are the causes of approximately 5% of all cancers in humans and one-third of all virus-induced tumors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In most previous studies, such as Chaozhou [Chen et al, ], Macao [Yip et al, ], Shanghai [Gu et al, ], and Zhejiang [Ye et al, ], as well as in Japan [Sasagawa et al, ], HPV‐52 was the most commonly identified type. While in some other reports from Henan [Shen et al, ], French [Casalegno et al, ] America [Wheeler et al, ], and other populations [Vinodhini et al, ; Wu et al, ], HPV‐16 was the most frequent type.…”
Section: Discussionmentioning
confidence: 99%